Borderline regionalisms in sociolect of Polish descent youth in Vilnius - Dawlewicz, Mirosław (Vilnius University Open Series, 2021)
The aim of the paper is introduction and analysis of regionalisms of Vilnian polish youth’s sociolect. Regionalisms and dialectical forms that are typical of Polish language of the North–Eastern Borderlands were given to the study. In the given collection the most substantial group constitutes lexical regionalisms. Morphological (word–formative and inflectional) and phonetical regionalisms appeared in the lower range. They represent different theme range. The analysis of regional lexeme meaning, given by the respondents, revealed that a part of them were used in their main regional meaning. However, there are frequent examples of neosemanticism that are used in a metaphorical meaning with a severe emotional tone.